Mémoires métisses de la guerre dans A Gesture Life de Chang-rae Lee - Michaël Taugis (Revue LISA)
Franklin Hata, the main character of A Gesture Life is a Japanese immigrant of Korean descent who seems to lead a peaceful life in a small American city but he is in fact haunted by his past as a medic in the Japanese army during World War II, by the crimes and atrocities perpetrated by soldiers and officers. Although the past and the present appear to be poles apart in his experience, they are interwoven in the novel, through the imagery of water and fire in particular. This interweaving shows that, to certain extent, his past experience in the war re-enacts itself in the present and it reveals the recurrent fraudulence which undermines his relationships with the other characters. This re-enactment also underlines the character’s problematic position as an often passive bystander and voyeuristic witness confronted with what war exposes: humane evil and vulnerability.